The effects of strategic management practices on customer satisfaction and loyalty in selected hotels in Kumasi - Bonsu, Charles; Owusu, Eric Edwin; Manuh, Adwoa Benewaa Brefo; Antwi, Emelda (Technium Social Sciences Journal, 2023)
Strategic management helps in making decisions about future opportunities and threats faced by the small and medium-sized enterprises. The main purpose of this study was to assess the effect of strategic management practices on the satisfaction and loyalty of customers of Hotels in Kumasi. Three objectives and accompanying research questions defined the scope of the study. The study adopted primary data which was solicited from two hundred respondents who were purposively sampled from selected hotels in Kumasi with a structured questionnaire on a five-point Likert Scale. Data collected were analyzed quantitatively using both descriptive and inferential statistics with SPSS version 21. Ordinary Least Squared (OLS) regression was adopted for the regression analysis. The study found out a positive effect on customer satisfaction hotels in Kumasi. Strategic Management Practices (SMP) suffused a coefficient of 0.046 in the regression model with a p-value of 0.0014 at 5% level of significance. Also, the study established a positive and significant relationship strategic management practices and customers loyalty of Hotels in Kumasi. The stud y recommends that hotels develop an organizational culture that reflects their business model since organizational culture will dictate how things should be run in the company and how individuals should act towards one another and clients in fulfilling the vision of the organization